Qualidade de vida de mães de crianças com microcefalia - Fernandes, Caren Cristina Freitas (2018)
Introduction: Microcephaly is a multifactorial malformation that is manifested by an inadequate development of the child's brain. This condition leads to motor and sensory disturbances that may have varied impairment. Rehabilitation cares for these children aim to minimize harms and promote harmony in the development of their organic functions. Culturally, family care is provided mainly by mothers, especially when there is specificity in this care, a condition that entails increasing daily tasks. The routine of consultations for diagnosis, treatment and rehabilitation may be associated with changes in the quality of life, since these mothers can give up their lives at the expense of child care. Caring for mothers of children with microcephaly is essential, since they are their main caregivers, can favor the continuity of these children's treatments and reduce family damage. Objective: to evaluate the quality of life of mothers of children with microcephaly compared to the quality of life of mothers with children of the same age but with normal neuropsychomotor development (NPM). Method: this study was a cross-sectional, comparative, analytical study held in a public reference service. Seventy-eight (78) mothers with children between birth and two years old, with and without changes in their NMP, were interviewed. The abbreviated Questionnaire for the Evaluation of Quality of Life (WHOQOL-bref) and a sociodemographic evaluation questionnaire, developed by the author, were used. The data were analyzed descriptively, evaluating the association between variables and correlation tests. Results: mothers of children with microcephaly showed lower scores for various quality of life domains, however there was only a statistically significant difference for the environmental domain (48.40 for the group of mothers of children with microcephaly vs. 57.13 for the group of mothers with children with normal NPM, P<0.02). It should be noted that there were also significant negative correlations between the majority obstetric variables, maternal age and quality of life scores. There was no significant association between the child’s age and such scores. Conclusion: the mothers of children with microcephaly were mostly residents of the interior and showed deficiency in some factors related to basic health needs. The fact that the children with neuropsychomotor variations have not influenced their mother’s quality of life, rather, the mother’s quality of life is affected predominantly by housing conditions and financial resources.